Hubungan Social Anxiety Terhadap Tingkat Kepercayaan Diri Pada Mahasiswa Baru Perantau Di Universitas Negeri Padang - Akrobi Imana; Hilmi Dzaki; Lingga Maya Putri; Rima Terra; Syarah Oletha Nabilah; Izzanil Hidayati (Observasi : Jurnal Publikasi Ilmu Psikologi, 2025)
This research investigates the connection between social anxiety and self-esteem among first-year students who have migrated from other regions to Universitas Negeri Padang. Employing a quantitative approach with a correlational design, the study included 44 migrant students as participants. Data were gathered through both online and face-to-face distribution of questionnaires. The statistical analysis indicated a significant negative relationship between social anxiety and self-esteem, with a correlation coefficient of -0.812 (p< 0.01). This finding demonstrates that higher levels of social anxiety are associated with lower levels of self-esteem among students, and conversely. The results highlight the influence of social anxiety on the social and psychological capacities of first-year migrant students. This study aims to offer valuable insights into the psychological challenges faced by migrant students and provide a foundation for creating interventions to enhance their well-being.